If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3x-15)=(2x-30)
We move all terms to the left:
(3x-15)-((2x-30))=0
We get rid of parentheses
3x-((2x-30))-15=0
We calculate terms in parentheses: -((2x-30)), so:We get rid of parentheses
(2x-30)
We get rid of parentheses
2x-30
Back to the equation:
-(2x-30)
3x-2x+30-15=0
We add all the numbers together, and all the variables
x+15=0
We move all terms containing x to the left, all other terms to the right
x=-15
| x*x+10=38 | | 4x-6=2×+10 | | 3x+(-1/8x)=23 | | -2/3y+12/7=8/11 | | -5v=-2v+6 | | -6z+10=4z | | u/2+15=33 | | 6v-8+11v=6(7v-10)-12(-2v+3) | | 4(5m+8)=3(2m-1) | | k−4=1 | | b2=1 | | 41=k=18 | | 6v-8+11v=6(7v-10)+12(-2v+3 | | 8x+16=8(x=2) | | 7c=5c-48 | | 7v+17-13v=-38 | | 225=4-3x | | -5(3b+12=-3b-5(b+12) | | 8x=x+5+16 | | 8=-6+7x | | 10x-135/2=4x | | 2=3a+5 | | x/2-8=24 | | C(x)=13.00+0.09x50 | | 6x+11+3x-2=180 | | M-22/4-7m-26/5=3 | | C(x)=13.00+0.09x | | 1/2(x+10)=7(x-1) | | (x+2)=2x-3 | | 0.7x-13=1.5x-17 | | k-356=17 | | 5−4x=65+11x |